Humanity-Oriented Character Strengths as Differential Predictors of Stigma Towards People with Special Educational Needs. (7th June 2023) - Datu, Jesus Alfonso; Tang, Robert; Xiaoying, Wu
ABSTRACT: Studies have consistently shown that character strengths predict well-being and positive psychological outcomes. However, there is sparse research on how these strengths relate to stigma towards individuals with special educational needs (SEN). This study addresses this gap through exploring the link of using humanity-oriented strengths (i.e., kindness, love, and social intelligence) to stigma and acceptance towards people with SEN via a cross-sectional design. A survey packet containing questionnaires about kindness, love, social intelligence, and stigma towards SEN, was administered to 210 Filipino undergraduate students. Results showed that gender positively predicted stigma towards SEN. Kindness negatively predicted stigma even after controlling for the effects of age and gender. Results suggest that promoting opportunities to cultivate kindness might serve as valuable approach to reduce negative and discriminatory attitude towards people with special needs.